“Exploring the Influence of Skill Variations, Job Autonomy, and Their Interaction on Changes in the Big Five Personality Dimensions Over Time” - liu, xingxing (My University, 2024)
Based on the job characteristics model and the Big Five theory of personality, the author proposed a model to suggest that skill varieties and job autonomy can drive changes in Big Five personality traits, particularly openness, conscientiousness, and agreeableness. Hypothesis 1 posited that exposure to diverse skills is associated with increases in these traits over time. Hypothesis 2 suggested that job autonomy similarly leads to increases in openness, conscientiousness, and agreeableness. Hypothesis 3 proposed that job autonomy moderates the relationship between skill variety and personality changes, with individuals experiencing high job autonomy and diverse skills exhibiting the most significant trait changes. Two waves of data from 3,246 employees over a five-year period from the Household, Income and Labour Dynamics in Australia Survey were analyzed. Skill variety, job autonomy, and Big Five personality traits were measured at various points throughout the study. The results showed that both skill variety and job autonomy positively predicted increases in openness, conscientiousness, and agreeableness over time. Additionally, the interaction between high job autonomy and skill variety was found to amplify these personality changes, with the most pronounced increases observed in individuals experiencing both high job autonomy and diverse skills. The implications for personality development and work design research are discussed.